2009
DOI: 10.1002/app.30623
|View full text |Cite
|
Sign up to set email alerts
|

Polymer crystallization and precipitation‐induced wrapping of carbon nanofibers with PBT

Abstract: Carbon nanofibers (CNFs) have attracted significant interest because of their excellent mechanical, electrical, and physical properties. Recent advances in chemical functionalization strategies are anticipated to extend their utility in various applications. In this study, noncovalent methods of CNF functionalization utilizing solution crystallization and precipitation techniques were used to create hybrid nanostructures consisting of CNFs and poly(butylene terephthalate) (PBT). Key to this study is the findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…With increasing concentration of the CNFs and thus increasing number of nuclei, the size of the spherulites should decrease, as observed in Figure 5. Similar effects of the concentration of the nanoparticles on crystallite size have been observed for other polymeric nanocomposites, i.e., nanocomposites based on high density polyethylene (HDPE),31 polyethylene (PE),23 Nylon‐6,6,32 poly (etheretherketone) (PEEK),33 and polybutylene terephthalate (PBT) nanocomposites 34. Overall, Figures 3–5 suggest that concentrations of both polymer and nanostructures, the latter acting as nucleating agents in the polymer solution, define the morphology and the size of the crystals that encapsulate the nanoparticles.…”
Section: Resultssupporting
confidence: 63%
“…With increasing concentration of the CNFs and thus increasing number of nuclei, the size of the spherulites should decrease, as observed in Figure 5. Similar effects of the concentration of the nanoparticles on crystallite size have been observed for other polymeric nanocomposites, i.e., nanocomposites based on high density polyethylene (HDPE),31 polyethylene (PE),23 Nylon‐6,6,32 poly (etheretherketone) (PEEK),33 and polybutylene terephthalate (PBT) nanocomposites 34. Overall, Figures 3–5 suggest that concentrations of both polymer and nanostructures, the latter acting as nucleating agents in the polymer solution, define the morphology and the size of the crystals that encapsulate the nanoparticles.…”
Section: Resultssupporting
confidence: 63%
“…Therefore, in early nucleation stage there is a competition between electrostatic interactions and the flexibility of the chains. It was reported by García-Gutiérrez et al [32] and Mago et al [33] that NHSK of PBT nanocomposites based on carbon nanostructures can be obtained by injection molding and precipitation processes. If the morphology obtained for PBT/SWCNT in our study is compared to that reported by other authors, it seems that, due to the fast nucleation rate of PBT, crystals growth is similar to that observed in polyethylene, that is, by forming lobules in early nucleation stage.…”
Section: Other Nucleation Mechanismsmentioning
confidence: 99%
“…The LPEI aggregates obtained via different cooling process were used for DSC analysis, and the typical heating curve was displayed in Figure 3 a. The integrated heat of fusion (denoted as S H ) on the heating curve was employed to judge the crystallinity [ 25 , 26 ]. By plotting the ratios of S H /S HO against m ice (where S H is based the samples obtained under the conditions in the presence of ice and S HO in the absence of ice), we compared the crystallinity of the LPEI aggregates.…”
Section: Resultsmentioning
confidence: 99%